Antecedents of Customer loyalty in Quick Restaurant Sector - Pabbi, Tejashwani; Narula, Sarang (International Journal of Psychosocial Rehabilitation, 2019)
The present study examines the relationship between customer service, commitment, communication, corporate image and trust with customer loyalty. The study was designed to develop the understanding of loyalty. Five antecedents were extracted as suggested by the review of literature. The empirical research has been conducted to find the affect of extracted antecedents on loyalty especially in quick service restaurants. An integrated model was developed and tested using the data collected from the customers of QSR in tri-city area of Chandigarh i.e. Chandigarh, Panchkula, Mohali. The result validates the effect of commitment, communication, corporate image and trust on loyalty. The study also validates opinion that the loyalty can be cultivated